Assessment of the Postoperative Appearance of the Rotator Cuff Tendon Using Serial Sonography After Arthroscopic Repair of a Rotator Cuff Tear. (1st July 2015) - Yoo, Hye Jin; Choi, Ja-Young; Hong, Sung Hwan; Kang, Yusuhn; Park, Jina; Kim, Sae Hoon; Kang, Heung Sik
Abstract : Objectives: The purpose of this study was to evaluate serial changes in sonographic findings of a rotator cuff tendon after rotator cuff repair. Methods: Sixty‐five arthroscopically repaired rotator cuff tears (43 full‐thickness tears and 22 partial‐thickness tears) were retrospectively included in this study. Serial sonographic examinations were performed at 5 weeks, 3 months, and 6 months after surgery. The sonographic findings of the repaired tendon were assessed for a recurrent tear, tendon thickness, morphologic tendon characteristics, vascularity, and bursitis at each time point. Results: Four recurrent tears occurred within 3 months of surgery. The postoperative tendon thickness decreased from 5 weeks to 6 months after surgery ( P = .001). There were significant changes in the morphologic tendon characteristics, including the echo texture, fibrillar pattern, and surface irregularity of the repaired tendon, from 5 weeks to 6 months after surgery ( P < .001). Additionally, subacromial‐subdeltoid bursitis and the vascularity of the repaired tendon decreased postoperatively over time. Conclusions: Serial sonography after arthroscopic rotator cuff repair was useful for monitoring the postoperative changes in a repaired tendon. The morphologic appearance of the repaired tendon and peritendinous soft tissue changes improved over time and nearly normalized within 6 months of surgery.